Subpopulations of regulatory T cells are associated with subclinical atherosclerotic plaques, levels of LDL, and cardiorespiratory fitness in the elderly - Tim Böttrich; Pascal Bauer; Vincent Gröβer; Magdalena Huber; Hartmann Raifer; Torsten Frech; Svenja Nolte; Theresa Dombrowski; Franz Cemic; Natascha Sommer; Robert Ringseis; Klaus Eder; et al. (Elsevier, 2024)
Background: Atherosclerosis forms the pathological basis for the development of cardiovascular disease. Since pathological processes initially develop without clinically relevant symptoms, the identification of early markers in the subclinical stage plays an important role for initiating early interventions. There is evidence that regulatory T cells (Tregs) are involved in the development of atherosclerosis. Therefore, the present study aimed to identify and investigate associations with Tregs and their subsets in a cohort of healthy elderly individuals with and without subclinical atherosclerotic plaques (SAP). In addition, various lifestyle and risk factors, such as cardiorespiratory fitness, were investigated as associated signatures. Methods: A cross-sectional study was performed in 79 participants (male: n = 50; age = 63.6 ± 3.7 years; body mass index = 24.9 ± 3.1 kg/m²; mean ± SD) who had no previous diagnosis of chronic disease and were not taking medication. Ultrasound of the carotids to identify SAP, cardiovascular function measurement for vascular assessment and a cardiorespiratory fitness test to determine peak oxygen uptake were performed. Additionally, tests were conducted to assess blood lipids and determine glucose levels. Immunophenotyping of Tregs and their subtypes (resting (rTregs) and effector/memory (mTregs)) was performed by 8-chanel flow cytometry. Participants were categorized according to atherosclerotic plaque status. Linear and logistic regression models were used to analyze associations between parameters. Results: SAP was detected in a total of 29 participants. The participants with plaque were older (64.8 ± 3.6 years vs. 62.9 ± 3.5 years) and had higher peripheral systolic blood pressure (133.8 ± 14.7 mmHg vs. 125.8 ± 10.9 mmHg). The participants with SAP were characterized by a lower percentage of rTregs (28.8% ± 10.7% vs. 34.6% ± 10.7%) and a higher percentage of mTregs (40.3% ± 14.7% vs. 30.0% ± 11.9%). Multiple logistic regression identified age (odds ratio (OR) = 1.20 (95% confidence interval (95%CI): 1.01-1.42)) and mTregs (OR = 1.05 (95%CI: 1.02-1.10)) as independent risk factors for SAP. Stepwise linear regression could reveal an association of peak oxygen uptake (β = 0.441), low-density lipoprotein (LDL) (β = -0.096), and SAP (β = 6.733) with mTregs and LDL (β = 0.104) with rTregs. Conclusion: While at an early stage of SAP, the total proportion of Tregs gives no indication of vascular changes, this is indicated by a shift in the Treg subgroups. Factors such as serum LDL or cardiopulmonary fitness may be associated with this shift and may also be additional diagnostic indicators. This could be used to initiate lifestyle-based preventive measures at an early stage, which may have a protective effect against disease progression.